Comparative nuclear matrix proteome analysis of skeletal muscle cells in different cellular states. (5th January 2021) - Puri, Deepika; Swamy, Ch V. B.; Dhawan, Jyotsna; Mishra, Rakesh K.
Abstract: The nuclear matrix (NuMat) serves as the structural framework for organizing and maintaining nuclear architecture, however, the mechanisms by which this non‐chromatin compartment is constructed and regulated are poorly understood. This study presents a proteomic analysis of the NuMat isolated from cultured skeletal muscle cells in three distinct cellular states— proliferating myoblasts (MBs), terminally differentiated myotubes (MTs), and mitotically quiescent (G0) myoblasts. About 40% of the proteins identified were found to be common in the NuMat proteome of these morphologically and functionally distinct cell states. These proteins, termed as the "core NuMat, " define the stable, conserved, structural constituent of the nucleus, with functions such as RNA splicing, cytoskeletal organization, and chromatin modification, while the remaining NuMat proteins showed cell‐state specificity, consistent with a more dynamic and potentially regulatory function. Specifically, myoblast NuMat was enriched in cell cycle, DNA replication and repair proteins, myotube NuMat in muscle differentiation and muscle function proteins, while G0 NuMat was enriched in metabolic, transcription, and transport proteins. These findings offer a new perspective for a cell‐state‐specific role of nuclear architecture and spatial organization, integrated with diverse cellular processes, and implicate NuMat proteins in the control of the cell cycle, lineage commitment, and differentiation.